1233: The Hospitallers in the Crown of Aragón Guarantee the Muslims of Cervera the Right to Remain (Transmediterranean History, 2021)
The article analyses a Carta de Poblament, in which the Hospitallers in Aragón and Catalonia guaranteed the Muslims of Cervera their living conditions, rights, and duties under Christian suzerainty after the Muslims' surrender in 1233. Based on this example, the article shows that such documents, created in the context of the so-called "Reconquista," usually resulted from extended negotiations. In these texts, the Muslim elites presented themselves as self-confident negotiating partners and were thus able to assert their community's claims to the free practice of religion and to ensure a high degree of administrative and legal autonomy vis-à-vis their new rulers.
Keywords: Carta de Poblament; Cervera del Maestre/Maestrat; Kingdom of Valencia; Knights Hospitaller; Mudejars (Mudéjares, mudèjars); Reconquista; Muslims under Christian rule; military orders